First record on the occurrence of long fingered gurnard Lepidotrigla longimana (Scorpaeniformes: Triglidae) from Bangladesh - Ahmed, Md Sagir; Mahjabin, Mysha; Antu, Durjoy Raha; Datta, Sujan Kumar (Journal of Bangladesh Academy of Sciences, 2023)
This study confirmed the presence of triglid fish Lepidotrigla longimana Li, (1981) for the first time in Bangladesh waters. Four individuals of this species were collected from Cox's Bazar (21.77 N 91.62 E) on 5 October 2018 as bycatch. The species was taxonomically identified through the traditional morphometric method which was further validated by a molecular approach based on partial cytochrome c oxidase subunit I (COI) sequences (DNA barcodes). The body length is three times of the head length and 4.1 times of the body height. Head length is 2.5 times larger than the snout length and 3.2 times of the eye diameter. The number of scales on the lateral line is 60. A smaller blue spot is present on the inner side of the pectoral fin. The average K2P distances of the COI sequence within species were 0.53. In the Maximum likelihood (ML) tree, the sequences clustered together under a single clade. Morphometric, meristic and molecular data thus confirmed the species as L. longimana. J. Bangladesh Acad. Sci. 47(1); 27-31: June 2023